Digital signal processing with Matlab examples. Volume 2, - Giron-Sierra, Jose Maria (Springer, 2017)
This is the second volume in a trilogy on modern Signal Processing. The three books provide a concise exposition of signal processing topics, and a guide to support individual practical exploration based on MATLAB programs. This second book focuses on recent developments in response to the demands of new digital technologies. It is divided into two parts: the first part includes four chapters on the decomposition and recovery of signals, with special emphasis on images. In turn, the second part includes three chapters and addresses important data-based actions, such as adaptive filtering, experimental modeling, and classification.
Keywords: MATLAB.; Signal processing -- Digital techniques.; elektronické knihy; electronic books